RITUAL TAGI JERE DALAM KOMUNITAS ETNIK KAO: PERAN LEMBAGA DEWAN ADAT DAN BADAN SYARA’ DAN PERKEMBANGANNYA - Mohammad Azzam Manan (LIPI Press, 2014)
Tagi jere is a ritual conducted by the Kao people in North Halmahera. It is a pilgrimage to a tomb (jere) believed as Shekh Masyur tomb, a religious traveller from Baghdad coming to Kao to preach Islam. The Kao people believe that the sacred tomb of Shekh Mansyur can be a mediation (Arabic: tawasul) to gain blessing and luck in order to achieve their hopes and dreams. This article describes the ritual process, both from cultural as well as social aspects, in which the Tribal Council (Dewan Adat) and Religious Council (Badan Syara’) play important roles. This article also draws the ritual from the mythology aspect and the social solidarity between the Kao people and other ethnic groups surrounding the tomb. Keywords: tagi jere, ethnic Kao, holy tomb, Tribal Council, Religious Council